Spotlight on daytime napping during early childhood - Horvath, K; Plunkett, KR (Dove Medical Press, 2018)
Daytime napping undergoes a remarkable change in early childhood, and research regarding its relationship to cognitive development has recently accelerated. In this review, we summarize our current understanding of this relationship focusing on children aged <5 years. First, we evaluate different studies on the basis of the experimental design used and the specific cognitive processes they investigate. Second, we analyze how the napping status of children may modulate the relationship between learning and napping. Third, the possible role of sleep spindles, ie, specific electroencephalographic components during sleep, in cognitive development is explored. We conclude that daytime napping is crucial in early memory development.